/5k + 1/ +/2x - 3/ =/4 + 3x/
Tìm x
/5k + 1/ + /2x - 3/ = /4 + 3x/
Tìm x
/5k + 1/ + /2x - 3/ = /4 + 3x/
e) ( x + 3)^3 = ( 2x) ^3
f) ( 5 - x )^5 = 32
g) ( 5x - 6)^3 = 64
h)5 . 9^x = 405
i) 11^5 : 11^ n - 2 = 11^5
k) ( 3x)^3 = ( 2x + 1)^3
e) \(\left(x+3\right)^3=\left(2x\right)^3\)
\(\Rightarrow x+3=2x\)
\(\Rightarrow2x-x=3\)
\(\Rightarrow x=3\)
f) \(\left(5-x\right)^5=32\)
\(\Rightarrow\left(5-x\right)^5=2^5\)
\(\Rightarrow5-x=2\)
\(\Rightarrow x=5-2\)
\(\Rightarrow x=3\)
g) \(\left(5x-6\right)^3=64\)
\(\Rightarrow\left(5x-6\right)^3=4^3\)
\(\Rightarrow5x-6=4\)
\(\Rightarrow5x=4+6\)
\(\Rightarrow5x=10\)
\(\Rightarrow x=\dfrac{10}{2}\)
\(\Rightarrow x=5\)
h) \(5\cdot9^x=405\)
\(\Rightarrow9^x=\dfrac{405}{5}\)
\(\Rightarrow9^x=81\)
\(\Rightarrow9^x=9^2\)
\(\Rightarrow x=2\)
i) \(11^5:11^{n-2}=11^5\)
\(\Rightarrow11^{n-2}=11^5:11^5\)
\(\Rightarrow11^{n-2}=1\)
\(\Rightarrow11^{n-2}=11^0\)
\(\Rightarrow n-2=0\)
\(\Rightarrow n=2\)
k) \(\left(3x\right)^3=\left(2x+1\right)^3\)
\(\Rightarrow3x=2x+1\)
\(\Rightarrow3x-2x=1\)
\(\Rightarrow x=1\)
Rút gọn :
1. (2x-5)(3x+1)-(x-3)^2+(2x+5)^2-(3x+1)^3
2. (2x-1)(2x+1)-3x-2)(2x+3)-(x-1)^3+(2x+3)^3
3. (x-2)(x^2+2x+4)-(3x-2)^3+(3x-4)^2
4. (7x-1)(8x+2)-(2x-7)^2-(x-4)^3-(3x+1)^3
5. (5x-1)(5x+1)-(x+3)(x^2-3x+9)-(2x+4)^2-(3x-4)^2+(2x-5)^3
6. (4x-1)(x+2)-(2x+5)^2-(3x-7)^2+(2x+3)^3=(3x-1)^3
1: \(=6x^2+2x-15x-5-x^2+6x-9+4x^2+20x+25-27x^3-27x^2-9x-1\)
=-27x^3-18x^2+4x+10
2: =4x^2-1-6x^2-9x+4x+6-x^3+3x^2-3x+1+8x^3+36x^2+54x+27
=7x^3+37x^2+46x+33
5:
\(=25x^2-1-x^3-27-4x^2-16x-16-9x^2+24x-16+\left(2x-5\right)^3\)
\(=8x^3-60x^2+150-125+12x^2-x^3+8x-60\)
=7x^3-48x^2+8x-35
Tìm x:
1) -3.(1-2x) - 4.(1+3x) = -5x + 5
2) 3.(2x - 5) - 6.(1 - 4x) = -3x + 7
3) (1 - 3x) - 2.(3x - 6) = -4x - 5
4) x.(4x - 3) - 2x.(2x - 1) = 5x - 7
5) 3x.(2x - 1) - 6x.(x + 2) = -3x + 4
6) (1 - 2x).3 - 4.(6x - 1) = 7x - 5
7) 6x - 3.(1 - 4x) - 5.(x + 1) = 2x + 7
8) 6.(1 - 3x) - 3.(2x + 5) = -10x + 7
9) 3x.(1 - 2x) + 6x^2 - 7x = 8.(1 - 2x) - 9
10) 2x.(1 + 3x) - 3x.(4 + 2x) = 3x - 4
* Trả lời:
\(\left(1\right)\) \(-3\left(1-2x\right)-4\left(1+3x\right)=-5x+5\)
\(\Leftrightarrow-3+6x-4-12x=-5x+5\)
\(\Leftrightarrow6x-12x+5x=3+4+5\)
\(\Leftrightarrow x=12\)
\(\left(2\right)\) \(3\left(2x-5\right)-6\left(1-4x\right)=-3x+7\)
\(\Leftrightarrow6x-15-6+24x=-3x+7\)
\(\Leftrightarrow6x+24x+3x=15+6+7\)
\(\Leftrightarrow33x=28\)
\(\Leftrightarrow x=\dfrac{28}{33}\)
\(\left(3\right)\) \(\left(1-3x\right)-2\left(3x-6\right)=-4x-5\)
\(\Leftrightarrow1-3x-6x+12=-4x-5\)
\(\Leftrightarrow-3x-6x+4x=-1-12-5\)
\(\Leftrightarrow-5x=-18\)
\(\Leftrightarrow x=\dfrac{18}{5}\)
\(\left(4\right)\) \(x\left(4x-3\right)-2x\left(2x-1\right)=5x-7\)
\(\Leftrightarrow4x^2-3x-4x^2+2x=5x-7\)
\(\Leftrightarrow-x-5x=-7\)
\(\Leftrightarrow-6x=-7\)
\(\Leftrightarrow x=\dfrac{7}{6}\)
\(\left(5\right)\) \(3x\left(2x-1\right)-6x\left(x+2\right)=-3x+4\)
\(\Leftrightarrow6x^2-3x-6x^2-12x=-3x+4\)
\(\Leftrightarrow-15x+3x=4\)
\(\Leftrightarrow-12x=4\)
\(\Leftrightarrow x=-\dfrac{1}{3}\)
d) (3x – 5)(7 – 5x) – (5x + 2)(2 – 3x) = 4 g) 3(2x - 1)(3x - 1) - (2x - 3)(9x - 1) =0 j) (2x – 1)(3x + 1) – (4 – 3x)(3 – 2x) = 3 k) (2x + 1)(x + 3) – (x – 5)(7 + 2x) = 8 m) 2(3x – 1)(2x + 5) – 6(2x – 1)(x + 2) = - 6
g: Ta có: \(3\left(2x-1\right)\left(3x-1\right)-\left(2x-3\right)\left(9x-1\right)=0\)
\(\Leftrightarrow3\left(6x^2-5x+1\right)-\left(18x^2-29x+3\right)=0\)
\(\Leftrightarrow18x^2-15x+3-18x^2+29x-3=0\)
\(\Leftrightarrow14x=0\)
hay x=0
Số chính phương chia năm dư mấy ?
Xét : 5k , 5k + 1 , 5k + 2 , 5k + 3 , 5k + 4
giải bất phương trình sau và biểu diễn tập nghiệm trên trục số
(3x-1)-2(2x+1)>2x-3,
1-2x+3(x+1)<3x+5
3-2x+2(-1-2x)>4x-6
4x+2-(2-4x)<2x+1
3x-(2x+1) > 2-3x
(2x-1)-3(1+5x) > 1-5x
3-4(-x-3) < 3x+4
(-1-3x)+(3x-4) > 4x-1
3(1-x)-4(2x+3) > 3-7x
6(2x-6)-3(-1-3x) > 2x+5
3x-4(-1-x) < 2x+5
3x-4(3x+2) < 5x-5
mai phải nộp mong ae giúp
1) |2x - 1| = 5
2) |2x - 1| = |x + 5|
3) |3x + 1| = x - 2
4) |3 - 2x| = x + 2
5) |2x - 1| = 5 - x
6) |- 3x| = x - 2
7) |2 - 3x| = 2x + 1
8) |2x - 1| + |4x ^ 2 - 1| = 0
9) (2x + 5)/(x + 3) + 1 = 4/(x ^ 2 + 2x - 3) - (3x - 1)/(1 - x)
10) (x - 1)/(x + 3) - x/(x - 3) = (7x - 3)/(9 - x ^ 2)
11) 5 + 96/(x ^ 2 - 16) = (2x - 1)/(x + 4) + (3x - 1)/(x - 4)
12) (2x)/(2x - 1) + x/(2x + 1) = 1 + 4/((2x - 1)(2x + 1))
13) (x + 2)/(x - 2) - 1/x = 2/(x ^ 2 - 2x)
14) x/(2x - 6) + x/(2x + 2) = (2x + 4)/(x ^ 2 - 2x - 3)